Morphological and histomorphometric evaluation of autogenous bone graft resorption in rabbits treated with alendronate sodium - Rosa, Teo Mario Da; Gerzson, Alexandre Da Silveira; Assis, Diogo Souza Ferreira Rubim De; Biguetti, Cláudia Cristina; Matsumoto, Mariza Akemi [UNESP]; GonÇales, Eduardo Sanches (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction Different rates of resorption are mediated by osteoclasts that may be affected by bisphosphonates during bone graft repair. Bisphosphonates are drugs that act as inhibitors of bone resorption.Objective The aim of the present study was to evaluate the rate of resorption of skullcap grafts in rabbits with and without the use of alendronate sodium.Material and method Thirty two New Zealand rabbits were divided into two groups (control group and alendronate group) and divided again into four periods (7, 14, 30 and 60 days). The control group did not receive alendronate, while animals of the experimental group received 4 mg of alendronate sodium weekly after the surgery. An 8 mm diameter bone block was removed from the parietal bone and fixed by screws to the contralateral parietal bone. During the periods of 7, 14, 30 and 60 days, the animals had undergone euthanasia and samples were removed for further analysis. Morphological and histomorphometric tests were used to compare graft thicknesses and to evaluate the newly formed bone at the interface between the graft and receptor site. The Wilcoxon and Mann-Whitney tests were used for statistical analyses.Result All grafts healed and integrated uneventfully and no statistically significant differences in resorption rates or bone deposition were detected after the final incorporation of the graft in both groups.Conclusion Alendronate Sodium did not decrease the bone graft resorption rates, but there was a tendency for better results in the control group regarding the resorption and neoformation in autogenous calvarial bone grafts in rabbits.

ResumoIntrodução Durante o reparo de enxertos ósseos, diferentes taxas de reabsorção são mediadas pelos osteoclastos e podem ser afetadas pelos bisfosfonatos, que são drogas que agem como inibidores da reabsorção óssea.Objetivo Avaliar a taxa de reabsorção dos enxertos ósseos de calota craniana de coelhos, com e sem o uso alendronato de sódio.Material e método Trinta e dois coelhos Nova Zelândia foram divididos igualmente em 2 grupos (grupo controle e grupo alendronato de sódio) e subdivididos em 4 períodos (7, 14, 30 e 60 dias). O grupo controle não recebeu alendronato, enquanto os animais do grupo experimental receberam 4 mg de alendronato de sódio por semana, em dose única, após a cirurgia. Um bloco de osso de diâmetro de 8 mm foi retirado o osso parietal e fixado com parafuso no osso parietal contralateral. Após cirurgia, nos períodos de 7, 14, 30 e 60 dias, os animais foram eutanasiados e as peças removidas para análise. Análises morfológica e histomorfométrica foram utilizados para comparar a espessura do enxerto e para avaliar a interface de osso recém formado entre o enxerto ósseo e o sítio receptor. Os testes de Wilcoxon e Mann-Whitney foram utilizados para as análises estatísticas.Resultado Todos os enxertos repararam e integraram sem intercorrências; não foram detectadas diferenças estatisticamente significativas nas taxas de reabsorção ou deposição óssea, após a incorporação final do enxerto em ambos os grupos.Conclusão Alendronato de sódio parece não diminuir a taxa de reabsorção, porém houve uma tendência de resultados melhores no grupo controle tanto na reabsorção quanto na neoformação óssea em enxertos ósseos autógenos de calota craniana de coelhos.
Avaliação morfológica e histomorfométrica da reabsorção de enxertos ósseos autógenos em coelhos usuários de alendronato de sódio
Keywords: Bone transplantation; alendronate sodium; bone resorption; Transplante ósseo; alendronato de sódio; reabsorção óssea